Corporate social performance and non‐financial reporting in the cruise industry: Paving the way towards UN Agenda 2030. (9th May 2022) - Di Vaio, Assunta; Varriale, Luisa; Di Gregorio, Angelo; Adomako, Samuel
Abstract: This article investigates the role of accounting disciplines in assessing and fostering corporate social performance (CSP) of business organisations to meet the UN Agenda 2030. Drawing from legitimacy theory, this qualitative study analyses if and how non‐financial reporting positively affects and fosters CSP practices and outcomes within the cruise industry. Specifically, using a case study methodology, a major cruise company has been analysed outlining its sustainable behaviour, through the manual content analysis of sustainability reports (2016–2017–2018), in achieving the sustainable development goals (SDGs) introduced by the UN Agenda 2030. The findings outline that the cruise company presents a clear sustainability and community orientation and adopts several initiatives, mostly focused on environmental and social issues, addressed to meet the 17 SDGs, where reputation and positive image have been recognised as the major antecedents in the perspective of CSP. This study contributes to the literature giving a broader and different reading of sustainability reporting as a "booster" of the CSP in meeting the SDGs and a further interesting application of the legitimacy theory, and offers managerial implications to systematise the content of non‐financial reporting by improving the quality of disclosure to achieve the SDGs, with focus on CSP processes, outcomes and ways.